2013
DOI: 10.1007/s12035-013-8425-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Toll Like Receptor (TLR) Radical Cycle in Chronic Inflammation: Possible Treatments Targeting the TLR4 Pathway

Abstract: Activation of the Toll-like receptor 4 (TLR4) complex, a receptor of the innate immune system, may underpin the pathophysiology of many human diseases, including asthma, cardiovascular disorder, diabetes, obesity, metabolic syndrome, autoimmune disorders, neuroinflammatory disorders, schizophrenia, bipolar disorder, autism, clinical depression, chronic fatigue syndrome, alcohol abuse, and toluene inhalation. TLRs are pattern recognition receptors that recognize damage-associated molecular patterns and pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
321
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 405 publications
(333 citation statements)
references
References 135 publications
6
321
0
6
Order By: Relevance
“…Recently, Lakey et al (2016) have shown that fine particulate matter containing redox-active transition metals, quinones and secondary organic aerosols can increase ROS concentrations in the lung lining fluid to levels characteristic for respiratory diseases. ROS play a central role in chemical transformation of biomolecules, such as proteins and lipids, in lung fluid to form damage associated molecular patterns (DAMPs), which can trigger immune reactions causing inflammation through the tolling receptor radical cycle (Lucas and Maes, 2013). Due to the important implications of adverse aerosol health effects, further studies are warranted to characterize and quantify EPFR and ROS contained in atmospheric aerosol particles in various locations, including highly polluted regions such as East Asia and India.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lakey et al (2016) have shown that fine particulate matter containing redox-active transition metals, quinones and secondary organic aerosols can increase ROS concentrations in the lung lining fluid to levels characteristic for respiratory diseases. ROS play a central role in chemical transformation of biomolecules, such as proteins and lipids, in lung fluid to form damage associated molecular patterns (DAMPs), which can trigger immune reactions causing inflammation through the tolling receptor radical cycle (Lucas and Maes, 2013). Due to the important implications of adverse aerosol health effects, further studies are warranted to characterize and quantify EPFR and ROS contained in atmospheric aerosol particles in various locations, including highly polluted regions such as East Asia and India.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that doses in the range of 0.075-2 Gy increased the expression of TLR4-MD2 in mouse macrophages (12). Additionally, TLR4 was shown to be involved in the induction of radiation resistance (19), cell proliferation and the promotion of radiation-induced lymphomas (20), as well as the promotion of reactive oxygen and nitrogen species (ROS/RNS) causing the aggravation of chronic inflammatory diseases (21). One of the novel activators of TLR4 is HMGB1 (22).…”
Section: Discussionmentioning
confidence: 99%
“…The consistency of this expressionphenotype pattern may have reflected a specific set of underlying molecular signaling responses that promote a granulocytic inflammatory response activated during suboptimal asthma control. Further inspection of the 316 replicated gene sets revealed two interrelated signaling pathways known to drive granulocytic inflammation: TREM-1, the triggering receptor expressed on myeloid cells 1 (26,27); and LPS. Expressed on monocytes, macrophages, and neutrophils, TREM-1 is an orphan immunoreceptor that amplifies inflammation induced by patternrecognition receptors (28) and interacts with the toll-like receptor 4 to promote LPS-mediated granulocytic inflammation (27,29).…”
Section: Novel Biologic Insights Into Asthma Controlmentioning
confidence: 99%